Studio Marconi : 1966/76 - Dieci anni in Italia. - Studio Marconi, Milano; Accame, Vincenzo; Argan, Giulio Carlo; Aspesi, Natalia; Bocca, Giorgio; Brera, Gianni; Buono, Oreste Del; Caroli, Flavio; Carrega, Ugo; Cerati, Roberto; Contessi, Gianni; Dorfles, Gillo; et al. (Milano : Studio Marconi, 1976)
Adami, Valerio ; Baj, Enrico ; Bello, Bruno Di ; Beuys, Joseph ; Blake, Peter ; Boetti, Alighiero ; Calder, Alexander ; Castellani, Enrico ; Ceroli, Mario ; Christo ; Coleman, James ; Colombo, Gianni ; Dias, Antonio ; Dorazio, Piero ; Hamilton, Richard ; Hsiao-Chin ; Keizo ; Man Ray ; Morellet, François ; Nevelson, Louise ; Novelli, Gastone ; Paolini, Giulio ; Pardi, Gianfranco ; Pezzo, Lucio Del ; Pistoletto, Michelangelo ; Pomodoro, Arnaldo ; Pomodoro, Gio ; Reuterswärd, Carl Fredrik ; Scanavino, Emilio ; Schifano, Mario ; Tadini, Emilio ; Tilson, Joe ; Uncini, Giuseppe ; Vaccari ; Wiley, William T.
Studio Marconi : exhibitions from 1966 to 1976 p. 121-123
Engels & Italiaans
boek
Keywords: Italië